213k views
2 votes
100 Pts!! HELP ASAP!!!!!!!!!

Write the equation of the graph shown below in factored form.
A. f(x) = (x − 3)2(x + 2)(x − 1)
B. f(x) = (x + 3)2(x − 2)(x + 1)
C. f(x) = (x + 3)2(x + 2)(x + 1)
D. f(x) = (x − 3)2(x − 2)(x − 1)

100 Pts!! HELP ASAP!!!!!!!!! Write the equation of the graph shown below in factored-example-1
User Smparkes
by
5.5k points

2 Answers

2 votes
I think the answer is D
User Anton Unt
by
5.4k points
6 votes

Answer:


\text{D. }f(x)=(x-3)^2(x-2)(x-1)

Explanation:

The equation below shows three zeroes at
x=1,
x=2,
x=3. By definition, these values of
x must yield a y-value of zero. Since the function bounces off of
x=3, there must be two occurrences of it.

Thus, the equation of this line, in factored form, is
\boxed{f(x)=(x-3)^2(x-2)(x-1)}

User Stef
by
6.0k points